Role and mechanism of NCAPD3 in promoting malignant behaviors in gastric cancer - Zhang, Su-Yun; Luo, Qiong; Xiao, Li-Rong; Yang, Fan; Zhu, Jian; Chen, Xiang-Qi; Yang, Sheng (Frontiers in Pharmacology, 2024)
Background: Gastric cancer (GC) is one of the major malignancies threatening human lives and health. Non-SMC condensin II complex subunit D3 (NCAPD3) plays a crucial role in the occurrence of many diseases. However, its role in GC remains unexplored.The Cancer Genome Atlas (TCGA) database, clinical samples, and cell lines were used to analyze NCAPD3 expression in GC. NCAPD3 was overexpressed and inhibited by lentiviral vectors and the CRISPR/Cas9 system, respectively. The biological functions of NCAPD3 were investigated in vitro and in vivo. Gene microarray, Gene set enrichment analysis (GSEA) and ingenuity pathway analysis (IPA) were performed to establish the potential mechanisms.Results: NCAPD3 was highly expressed in GC and was associated with a poor prognosis.NCAPD3 upregulation significantly promoted the malignant biological behaviors of gastric cancer cell, while NCAPD3 inhibition exerted a opposite effect. NCAPD3 loss can directly inhibit CCND1 and ESR1 expression to downregulate the expression of downstream targets CDK6 and IRS1 and inhibit the proliferation of gastric cancer cells. Moreover, NCAPD3 loss activates IRF7 and DDIT3 to regulate apoptosis in gastric cancer cells.Our study revealed that NCAPD3 silencing attenuates malignant phenotypes of GC and that it is a potential target for GC treatment.